IBD Patients’ Perception of Severe Acute Respiratory Syndrome Coronavirus 2 Pandemic and Satisfaction with Provided Healthcare: A Cross-Sectional Study - Hrabar, Davor; Cacic, Petra; Biscanin, Alen; Tomasic, Vedran; Kralj, Dominik; Ogresta, Doris; Pelajic, Stipe; Dorosulic, Zdravko; Babarovic, Toni (Turkish Journal of Gastroenterology, 2022)
Background: Severe acute respiratory syndrome coronavirus 2 pandemic is affecting public health systems and mental health significantly. Patients with inflammatory bowel disease are witnessing vigorous organizational changes in inflammatory bowel disease centers and experiencing all psychosocial effects of the crisis. We conducted a single-center cross-sectional study in order to assess inflammatory bowel disease patients’ concerns, behavior, and satisfaction with provided healthcare during severe acute respiratory syndrome coronavirus 2 pandemic. Methods: All inflammatory bowel disease patients treated in our center from April 1 to June 1, 2020, were invited to fulfill an anonymous online questionnaire. Results: A total of 132 participants have completed the questionnaire, 63.2% were female, 57.9% had Crohn’s disease (CD) During the first wave of the pandemic, 74.2% of participants perceived themselves as a high-risk group for acquiring coronavirus disease 2019 only because they suffered from inflammatory bowel disease, and 66.2% thought inflammatory bowel disease medications make them more susceptible to coronavirus disease 2019. This especially concerned patients treated with biologics (B = 2.068, P < .01). Females were more stressed (B = −1.451, P < .01) and concerned (B = −1.488, P < .01) about the pandemic, and they also reported more potential benefits from professional psychological help (B = −2.664, P = .02). Six patients (5.3%) discontinued inflammatory bowel disease therapy on their own initiative. Seventy-eight (68.4%) patients were completely satisfied and 14 (12.3%) were partially satisfied with the quality of healthcare provided in our inflammatory bowel disease center. Conclusion: Female inflammatory bowel disease patients tend to be more emotionally vulnerable during severe acute respiratory syndrome coronavirus 2 pandemic. Although psychological support should be continuously available to all inflammatory bowel disease patients, female gender may warrant special attention. Providing patients with adequate and early information during pandemic probably leads to better compliance and higher satisfaction. Cite this article as: Hrabar D, Cacic P, Biscanin A, et al. IBD patients’ perception of severe acute respiratory syndrome coronavirus 2 pandemic and satisfaction with provided healthcare: A cross-sectional study. Turk J Gastroenterol. 2022;33(3):190-195.